Assessing the impact of an online dementia awareness initiative co‐created with and for English, Arabic and Vietnamese speaking communities: A case study - Yousra Ali; Gabriela E. Caballero; Eman Shatnawi; Ann Dadich; Genevieve Z. Steiner‐Lim; Canterbury Bankstown Dementia Alliance; Michelle DiGiacomo; Diana Karamacoska (Wiley, 2024)
Abstract Background Awareness and understanding of dementia remain limited in ethnically diverse populations in multicultural societies due to culturally inappropriate and inaccessible information. Objective To establish the impact, helpers and hinderers of an online multilingual dementia awareness initiative co‐created with and for English, Arabic and Vietnamese speaking people. Design A case study using mixed methods to assess the impact and implementation of an information session on dementia knowledge. Setting and Participants The study was conducted with English, Arabic and Vietnamese speaking individuals in Canterbury‐Bankstown, Australia. Intervention Studied A dementia alliance co‐created an online multilingual dementia information session, which was delivered synchronously in English, Arabic and Vietnamese by trained facilitators. Main Outcome Measures In‐session group discussions, quizzes and a postsession survey assessed the impact on dementia knowledge. A postimplementation focus group explored the factors that helped and hindered the initiative. Results The online dementia information session successfully supported participants understanding of dementia causes, impacts and care strategies. The initiative was hindered by competing priorities and limited accessibility to target audiences, while it was helped by the support of an established organisation and feedback mechanisms. Discussion Ongoing dementia education and awareness‐raising campaigns that are culturally sensitive are needed in communities to promote dementia literacy and help‐seeking. Conclusions An online multilingual dementia information session can be an effective way to improve dementia literacy and advocate for change in multicultural communities. Patient or Public Contribution English, Arabic and Vietnamese speaking members of the Canterbury Bankstown Dementia Alliance participated in the co‐creation and evaluation of this initiative.